1992
DOI: 10.1007/bf00009604
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the Thelastomatoidea, Oxyurida of invertebrate hosts III. Hystrignathidae

Abstract: The family Hystrignathidae (Thelastomatoidea, Oxyurida, Nematoda) is revised . The following genera are included in the family :

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
5

Year Published

1994
1994
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 8 publications
0
42
0
5
Order By: Relevance
“…However, morphological characteristics can cause misidentification, as when Chitwood (1932) erected the genus, he indicated that the female reproductive system was amphidelphic. Later, Adamson and Van Waerebeke (1992) diagnosed the genus and indicated that it was prodelphic. The 18S rDNA sequence of H. indicus shows 95% identity with related species such as L. portentosae, T. gueyei, and T. krausi and provides strong molecular evidence.…”
Section: Resultsmentioning
confidence: 99%
“…However, morphological characteristics can cause misidentification, as when Chitwood (1932) erected the genus, he indicated that the female reproductive system was amphidelphic. Later, Adamson and Van Waerebeke (1992) diagnosed the genus and indicated that it was prodelphic. The 18S rDNA sequence of H. indicus shows 95% identity with related species such as L. portentosae, T. gueyei, and T. krausi and provides strong molecular evidence.…”
Section: Resultsmentioning
confidence: 99%
“…For each parasite sample, ceacum fluid were recovered and stored as mentioned above. Males and females nematode were identified with confidence to their morphological characters, and according to Basir (1956) and Adamson & van Waerebeke (1992).…”
Section: Parasite Recoverymentioning
confidence: 99%
“…Their taxonomy and phylogenetic relationships still remain confused, particularly for invertebrate parasites (Adamson, 1989;Adamson & Van Waerebeke, 1992), and we suspect numerous cases of synonymy. These parasites have a haplo-diploid mode of reproduction and show a female-biased sex-ratio (Adamson, 1989).…”
Section: Introductionmentioning
confidence: 96%
“…The study of this family revealed the presence of various species (Adamson and Van Waerebeke 1992). One of these genera is Leidynema, which was first described by Schwenk (in Travassos 1929), with L. appendiculatum (Leidy, 1850) as type species.…”
Section: Introductionmentioning
confidence: 99%
“…One of these genera is Leidynema, which was first described by Schwenk (in Travassos 1929), with L. appendiculatum (Leidy, 1850) as type species. This is characterized by having a gut diverticulum and by the arrangement of the genital papillae in the male, with four pairs of genital papillae, one large ventral pre-anal and three subventral and postanal (Adamson and Van Waerebeke 1992). At present, six species belonging to this genus have been reported: L. appendiculatum (Leidy 1850) Chitwood 1932, L. delatorrei Chitwood 1932, L. periplaneti Farooqui 1967, L. portentosae Van Waerebeke 1978, L. schwenkei Farooqui 1967, and L. socialis (Leidy, 1850 Adamson and Van Waerebeke 1992.…”
Section: Introductionmentioning
confidence: 99%